1972
DOI: 10.1002/cjce.5450500213
|View full text |Cite
|
Sign up to set email alerts
|

Pressure drop in a mobile‐bed contactor

Abstract: The overall pressure drop and the vertical static pressure profile in a 0.14‐m. diameter mobile‐bed contactor have been investigated for two packing sizes and three packing heights. The gas and liquid flow rates were the two other variables studied. Foam polystyrene spheres were used as packings. The relationship between the static pressure and vertical position of the bed was found to be linear. A correlation of the drag parameter with Gg, Gt and Lp is presented. States of fully‐mobile bed operation are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…If the particle density is low enough (pp < 170 kg/m3), the bed will fluidize before the loading point is reached. Figure 3 shows this case using the data of Chen and Douglas (1968), Tichy et al (1972), and Tichy and Douglas (1972) to illustrate the point. Note that the pressure drop becomes constant and the liquid holdup remains the same as that in the packed bed at gas velocities in excess of the minimum.…”
Section: Resultsmentioning
confidence: 95%
“…If the particle density is low enough (pp < 170 kg/m3), the bed will fluidize before the loading point is reached. Figure 3 shows this case using the data of Chen and Douglas (1968), Tichy et al (1972), and Tichy and Douglas (1972) to illustrate the point. Note that the pressure drop becomes constant and the liquid holdup remains the same as that in the packed bed at gas velocities in excess of the minimum.…”
Section: Resultsmentioning
confidence: 95%
“…Using the works of many authors, 12,14,18,20,[25][26][27][28][29][30][31] devoted to these pressure drops, we obtained the following relation: (12) where the dimensionless Re b is obtained by the following relation: 24 (13) is a dimensionless group considering a specific gas flow rate m = U g /h 1 (m in s −1 ), γ l is the kinematic viscosity of the liquid in m 2 s −1 , and…”
Section: Determination Of Pressure Drop ∑(−δP F )mentioning
confidence: 99%
“…3 Results and discussion we observed that the evolution of total pressure drop through the column with the different operating variables (u g , φ, H st ,) was similar to that reported by different authors. 12,13,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][27][28][29][30][31][32][33][34][35][36][37] The variation of the expansion bed (H d /H st ) with the gas superficial velocity (u g ) at constant liquid velocity (u l ) is presented in Fig. (3).…”
Section: Determination Of Pressure Drop ∑(−δP F )mentioning
confidence: 99%
See 1 more Smart Citation
“…The early work on turbulent bed contactors introduced considerable confusion as different authors found that changing particle properties and gas and liquid flow rates influenced the minimum mobilisation velocity and total pressure drop across the bed in different ways (Adamiec et al, 1976;Askelrod and Yakovenko, 1969;Barile and Mayer, 1971;Blyakher et al, 1967;Davidson and Harrison, 1963;Chen and Douglas, 1968;Gel'perin et al, 1966b;Gel'perin et al, 1968;Handl, 1976;Tichy et al, 1972;Vetlugina et al, 1976). This confusion was dispersed by O'Neill et al (1972) who identified four different flow regimes which can exist in countercurrent gas-liquid contactors.…”
mentioning
confidence: 99%